Shorter telomere length in COPD cases secondary to biomass-burning smoke exposure - Angélica Domínguez-de-Barros; Gloria Pérez-Rubio; Ingrid Fricke-Galindo; Alejandra Ramírez-Venegas; Malena Gajate-Arenas; Rafael Hernández-Zenteno; Salvador García-Carmona; Robinson Robles-Hernández; María E. Ramírez-Díaz; Filiberto Cruz-Vicente; María L. Martínez-Gómez; Jacob Lorenzo-Morales; et al. (Respiratory Research)
Abstract Background Chronic obstructive pulmonary disease (COPD) is characterized by progressive airflow obstruction and destruction of lung tissue, primarily attributed to tobacco smoking. However, other factors like biomass-burning smoke (BS) exposure are also implicated. COPD has been described as an accelerated aging disease, and telomere length is a biomarker of aging. Methods This study examined telomere length in 189 Mexican individuals, from which 93 developed COPD secondary to BS exposure (BE-COPD); the rest of the participants were exposed to BS but did not develop the disease. Lung function parameters were measured by spirometry, and relative telomere length (rTL) from peripheral blood DNA was determined using multiplex qPCR. Results Results showed rTL to inversely correlate with age (R2=-0.207, p = 0.006) and with the hours-a-day of BS exposure (R2=-0.297, p < 0.001). Within BE-COPD cases, rTL was associated with daily BS exposure, and BE-COPD individuals exhibited a reduced rTL compared to controls (1.39 ± 0.45 vs. 0.89 ± 0.50; p < 0.001). When compared by rTL length in BE-COPD cases, longer telomeres were associated with decreased COPD risk (β = 0.134, 95% CI = 0.053–0.339; p < 0.001). However, no significant relationship was found between rTL and clinical or lung function parameters in the BE-COPD group. Conclusions This is the first study to document that individuals with COPD secondary to biomass smoke exposure present shorter telomeres than BS-exposed subjects who did not develop the disease.